PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT.PERKEBUNAN NUSANTARA VI (PERSERO) UNIT USAHA OPHIR - Nur Hamzah (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2016)
This study was intended to see the influence of Organizational Climate and Organizational Commitment toward Employees’ Performance at PT. PN VI. The populations in this study were as many as 38 people, where the sampling techniques using surveying techniques. From the results of this study, the variables were Organizational Climate (X1) and Organizational Commitment (X2) significantly affects employees’ performance (Y) with a significant level of 0.000. The magnitude of the effect of Organizational Climate (X1) and Organizational Commitment (X2) the Employees’ Performance (Y) was 0.671 (R2 = 67.1). Test f an independent variable showed both positive and gave significant effect on the dependent variable amounted to 89 122. Keywords: Organizational Climate, Organizational Commitment, Employees’ performance